Dissemination of Environmental Information in the E-Governance system: World Trends and Experience for Ukraine - Ladychenko, Viktor; Chomakhashvili, Olena; Uliutina, Olena; Kanaryk, Julia (European Journal of Sustainable Development, 2020)
The UN E-Government Survey 2016 on «E-Government in Support of Sustainable Development» offers a brief overview of e-government trends in the world. According to the survey, more and more governments are using information technology to provide services and engage people in decision-making processes in rural areas in their countries. Talking about the emerging economies in East Europe, the Ukrainian economy is growing faster with 50% of population living in rural areas, which develops incredible pressure on the government to give more focus on many ways of environmental safety of Ukraine. Ukraine is predominantly rural country and in order to improve the environmental conditions it is important that both central and local governments carried out national environment information activity. Modern information technology helps to disseminate environmental information in rural areas and is a major provider of information opportunities for the rural population. By 2020 Ukrainian government has a goal to achieve interaction at all levels by electronic mode. There are various electronic databases that are already functioning at the national level such as the Real Estate Register, Public Cadastral Map, etc. that can help the Ukrainian government to achieve greater transparency and successful governance. However, access to such registers is currently not possible for regional communities. Therefore, disposing of environmental information, avoiding environmental threats to the local population and enhancing the effectiveness of local governance is a goal for local governments. This paper offers a modern vision of information technologies in the field of natural resources management. E-government projects and ways to solve problems in the sphere of dissemination of information in rural areas in order to improve e-governance in contemporary Ukraine were explored. Keywords: Environmental information, information human rights, sustainable development, EU environmental policy